DEVELOPMENT AND VALIDATION OF CHEMOMETRIC ASSISTED SPECTROPHOTOMETRIC TECHNIQUE FOR SIMULTANEOUS ESTIMATION OF CINITAPRIDE AND PANTOPRAZOLE FROM BULK AND COMBINED DOSAGE FORM (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
This paper describes two sensitive, accurate and precise chemometric spectrophotometric methods for the simultaneous determination of Cinitapride hydrogen tartarate (CNT) and Pantoprazole sodium (PANTO) in bulk powder and capsules without prior separation. Multivariate calibration chemometric methods are proposed for simultaneous determination of CNT and PANTO. The chemometric methods applied are Principal Component Regression (PCR) and Partial Least Squares (PLS). These approaches are successfully applied to quantify both drugs using the information included in the absorption spectra of appropriate solutions. In these multivariate methods, calibration sets of standard samples composed of different mixtures of CNT and PANTO have been designed. The methods were validated according to The International Conference on Harmonization (ICH) guidelines. The specificity of the proposed methods was tested using laboratory-prepared mixtures. The developed methods were successfully applied for the determination of CNT and PANTO in bulk powder and dosage form combination.